(untitled) (Universal International Scientific Journal, 2026)
This article discusses the methodological foundations of the use of digital technologies in the process of teaching radiology in higher medical education institutions. The issues of strengthening students’ theoretical knowledge, developing practical skills, and increasing the effectiveness of independent learning through the introduction of modern information and communication technologies into the educational process are analyzed. Also, the pedagogical possibilities of using virtual laboratories, simulators, electronic learning platforms, multimedia resources, and programs based on artificial intelligence in teaching radiology are considered. Methods for modeling clinical cases, analyzing images, and forming diagnostic decision-making competencies using digital technologies are substantiated. The results of the study show that the use of innovative approaches in teaching radiology serves to increase the quality of education and student activity. This work contains practical recommendations for improving the digital educational environment in higher medical education institutions and introducing modern pedagogical technologies into the educational process